PENERAPAN KBAT DALAM PROSES PDPC PENULISAN KARANGAN BAHASA MELAYU SPM - Nyuk Phin, Bong; Zuraini, Seruji; Roslan, Haji Ali (Universiti Malaya, 2025)
This research was conducted to explore the students’ ability to use High Order Thinking Skills (HOTs) in teaching and facilitating SPM Bahasa Melayu essay writing. Four Bahasa Melayu teachers who teach Form 4 and 5 were chosen as the samples for this research. This research was done in one secondary IB school (International Baccalaureate) in Samarahan Division, Sarawak. The research objective is to determine how a teacher uses HOTs in the pre-teaching and facilitating, during teaching and facilitating and post-teaching and facilitating in SPM Bahasa Melayu essay writing. Data was collected by interviewing and analysing the documents that involved the students’ work. The data was analysed thematically to get the relevant themes to answer the research question. The three themes obtained to answer the research question were (i) Pre-teaching and facilitating in SPM Bahasa Melayu essay writing based on HOTs, (ii) during teaching and facilitating in SPM Bahasa Melayu essay writing based on HOTs, and (iii) post-teaching and facilitating in SPM Bahasa Melayu essay writing based on HOTs. The research finding showed that in teaching and facilitating, the SPM essay writing process based on Hots was used in pre-teaching and facilitating, during teaching and facilitating and post-teaching and facilitating. The implementation of HOTs procedure in learning and facilitating Bahasa Melayu essay writing, which was formed based on the outcome of this research, can be used by Bahasa Melayu teachers as guidelines in teaching essay writing.